Complex Treatment of Children Affected by Undifferentiated Connective Tissue Dysplasia Combined with Bone Mineral Density Reduction - Akhmetzhanova, Dinara O. (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Undifferentiated connective tissue dysplasia has a number of common mechanisms with inadequate bone formation, including lack of its mineralization in childhood. The frequency of combinations of connective tissue dysplasia with osteopenia and osteoporosis is quite high, which leads to the hypothesis of the advisability of complex treatment of such combinations. The purpose of the research is to develop and evaluate the clinical effectiveness of the integrated treatment of connective tissue dysplasia and osteopenic syndrome in children. Materials and Methods: We examined 160 children aged 3–16 years, divided into 2 groups that were identical in number and age and sex content. Undifferentiated connective tissue dysplasia and reduced bone mineral density (BMD) were diagnosed in all children included in the study. The concentration of 25-hydroxyvitamin D, calcium, and magnesium in the blood and excretion of glycosaminoglycans (GAGs) were determined. Ultrasonic densitometry of the calcaneus was performed. Patients were under prospective observation for 2 years. In the comparison group, calcium and Vitamin D3 preparations were administered in the age-related therapeutic dosage during 6 months, followed by a change to prophylactic doses. In the main group, in addition to Vitamin D3 and calcium, a preparation of sodium chondroitin sulfate was given within 3 months, and after a break of 6 months, a 3-month course was repeated, as well as a magnesium preparation in the age-related therapeutic dosage, the duration of the course was 6 months, with a change to a prophylactic dose until the end of observation. Research Findings: The t-test level for densitometry in the main group increased more rapidly than in the comparison group. The significance of differences with the control group was absent after 18 and 24 months of treatment. After 24 months, significant differences in favor of the main group were determined by the rate of normalization of the BMD level (χ2 = 11.90, P = 0.015). At the same time, there were no significant differences in the content of the metabolite of Vitamin D and calcium in the blood. In contrast, magnesium content after 6 months revealed significant differences between groups of children with pathology in favor of the main group, which persisted until the end of the study. The decrease in GAG excretion in the study dynamics was revealed only in the children of the main group. This process continued after 6 months and at least up to 9 months, and during the entire observation period from 6 to 24 months, this indicator was lower in the main group than in the comparison group. Conclusions: (1) The use of complex treatment of children affected by undifferentiated connective tissue dysplasia in combination with BMD reduction helps to increase BMD and in a significant number of cases (over 20%) contributes to full normalization of BMD within 2 years. (2) Complex treatment also provides correction of pathogenetic mechanisms of connective tissue disease, which should have a positive effect on the state of connective tissue and its adequate formation in the case of timely administration of therapy.